Clitocine reversal of P-glycoprotein associated multi-drug resistance through down-regulation of transcription factor NF-κB in R-HepG2 cell line. - Jianguo Sun (Public Library of Science (PLoS), 2012)
Multidrug resistance (MDR) is one of the major reasons for failure in cancer chemotherapy and its suppression may increase the efficacy of therapy. The human multidrug resistance 1 (MDR1) gene encodes the plasma membrane P-glycoprotein (P-gp) that pumps various anti-cancer agents out of the cancer cell. R-HepG2 and MES-SA/Dx5 cells are doxorubicin induced P-gp over-expressed MDR sublines of human hepatocellular carcinoma HepG2 cells and human uterine carcinoma MES-SA cells respectively. Herein, we observed that clitocine, a natural compound extracted from Leucopaxillus giganteus, presented similar cytotoxicity in multidrug resistant cell lines compared with their parental cell lines and significantly suppressed the expression of P-gp in R-HepG2 and MES-SA/Dx5 cells. Further study showed that the clitocine increased the sensitivity and intracellular accumulation of doxorubicin in R-HepG2 cells accompanying down-regulated MDR1 mRNA level and promoter activity, indicating the reversal effect of MDR by clitocine. A 5'-serial truncation analysis of the MDR1 promoter defined a region from position -450 to -193 to be critical for clitocine suppression of MDR1. Mutation of a consensus NF-κB binding site in the defined region and overexpression of NF-κB p65 could offset the suppression effect of clitocine on MDR1 promoter. By immunohistochemistry, clitocine was confirmed to suppress the protein levels of both P-gp and NF-κB p65 in R-HepG2 cells and tumors. Clitocine also inhibited the expression of NF-κB p65 in MES-SA/Dx5. More importantly, clitocine could suppress the NF-κB activation even in presence of doxorubicin. Taken together; our results suggested that clitocine could reverse P-gp associated MDR via down-regulation of NF-κB.